Surgical Drainage Cystogastrostomy in Patient with Pancreatic Pseudocyst - Agung Ary Wibowo; Tjahyo Kelono Utomo; Henderi Saputra; Yohelio Priawan Sibu; Kenanga Marwan Sikumbang (Program Studi Ilmu Bedah, Fakultas Kedokteran Universitas Udayana, 2023)
Background: Pancreatic pseudocysts are often managed through surgical drainage, which is common in rural areas for several reasons, including limited facilities. Case: Therefore, this study presents a successful treatment of three pancreatic pseudocyst cases using surgical drainage cystogastrostomy. Furthermore, this treatment method was selected due to the ease of performance in rural hospitals and was successfully performed without any complications. Conclusion: The diagnoses of pancreatic pseudocysts were confirmed by anamnesis, physical examination, and CT-scan imaging. The operations were also performed successfully without any complications. However, the patients will also undergo follow-up for two years to enable the doctors to observe for any possible long-term complications.